Refeeding syndrome in patients with anorexia nervosa - case reports - Stanicki, Paweł; Szukała, Klaudia; Szypłowska, Małgorzata; Dzikowski, Michał (Current Problems of Psychiatry, 2021)
Introduction. Refeeding syndrome RS is a life-threatening acute hormonal and metabolic disorder that occurs in patients with moderate or severe malnutrition as a result of improperly administered nutritional therapy.Material and method. The aim of this study is to describe the cases of two female patients suffering from anorexia nervosa, who developed a refeeding syndrome after starting nutritional therapy. Additionally, the available literature was reviewed in order to characterize the issue, including negative consequences and prevention of the refeeding syndrome.Results. In both cases, the development of the refeeding syndrome was found in the patients, resulting from the excessive supply of energy and nutritional substrates in a short time, preceded by a previous, months long period of starvation and exhaustion of the organism (both patients had a decrease in the body mass index - BMI - to the value of about 14 kg/m2). In patient 1, the symptoms concerned mainly the cardiovascular system: a significant increase in the concentration of N-terminal B-type natriuretic propeptide (NT-proBNP) and tachycardia, as well as a decrease in the concentration of inorganic phosphates and hypokalemia. On the other hand, in the case of patient 2, symptoms such as confusion or deep disturbances of consciousness, which led to hospitalization in the intensive care unit, dominated the clinical picture.Conclusions. Refeeding syndrome may develop during nutritional rehabilitation, especially in the case of a sudden, inadequately planned supply of nutrients. Particular care should be taken in patients with extremely low BMI when reintroducing nutrition. The presented case reports draw attention to the possibility of cardiological complications and mental disorders of the realimentation syndrome, and indicate the behavior of patients (eating excessive food) that may lead to the development of the refeeding syndrome.